KOMPARASI HUKUM IJAB QOBUL YANG DIWAKILKAN PERSPEKTIF MADZHAB SYAFI’I DAN KOMPILASI HUKUM ISLAM (KHI) - Nuroniah Fauziyatul Fadhilah; Habibi Al Amin (JURNAL ILMIAH NUSANTARA, 2025)
This study examines the comparative legal perspective on the implementation of ijab qabul (offer and acceptance) through the mechanism of representation (wakalah) in marriage contracts, based on the views of the Shafi’i school of thought and the Compilation of Islamic Law (KHI). Ijab qabul is a fundamental element of marriage that must be fulfilled for the contract to be considered valid under Islamic law. In practice, not all parties involved in the marriage can be present in person, making representation a permissible and recognized solution in Islamic jurisprudence. However, there are differences regarding the limitations, conditions, and validity of wakalah between classical Shafi’i fiqh and the formal provisions of the KHI. This research utilizes a qualitative descriptive methodology combined with a normative juridical approach, using library research on classical Shafi’i literature and the relevant provisions in the KHI. Primary data are sourced from classical fiqh books such as I’anatu Thalibin, Al-Umm, Fathul Qarib, and Hasyiyah al-Bajuri, while secondary data are obtained from journals, books, and other legal documents. The findings indicate that both the Shafi’i school and the KHI permit the use of representatives in performing ijab qabul, provided certain conditions are met. According to the Shafi’i school, the appointment of a representative must be explicit, and the ijab qabul utterance must clearly state that the contract is being conducted on behalf of the person granting the authority. Meanwhile, the KHI, in Article 29 paragraph 2, allows wakalah in marriage contracts either orally or in writing, provided that the representative meets Islamic legal requirements and explicitly declares that they are acting on behalf of the authorizing party. The study concludes that there is no fundamental contradiction between the Shafi’i school and the KHI regarding the permissibility of delegated ijab qabul. The differences lie only in technical and administrative aspects. Both legal systems aim to facilitate the Muslim community in conducting valid marriage contracts, while ensuring compliance with both Islamic and formal legal standards).